2015
DOI: 10.3329/bjmed.v25i1.25071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Homocysteine and Ischemic Stroke

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Only articles rated good are reported on and discussed in this article. Studies rated fair 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 and poor 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only articles rated good are reported on and discussed in this article. Studies rated fair 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 and poor 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95…”
Section: Resultsmentioning
confidence: 99%
“…Five studies showed an association between small-and large-vessel diseases when subclassifying stroke using the 71 Kelly et al ( 2004) 31 Alkali et al (2006) 131 Kim et al (2011) 32 Araki et al (1989) 72 Kim et al (2011) 33 Fekih-Mrissa et al (2013) 80 Kristensen et al (1999) 34 Ma et al (2017) 42 Lee et al ( 2008) 36 Sun et al ( 2005) 95 Li et al (2018) 38 Tas et al ( 2005) 96 Lu et al (2018) 40 Yi et al (2013) 101 Luo et al (2017) 41 Yingdong et al (2002) 102 Ma et al (2011) 43 Cross-sectional studies Mao and Han (2018) 44 Adunsky et al (2000) 69 Meiklejohn et al (2001) 45 Ben-Salem et al (2010) 73 Modi et al ( 2005) 47 Brattström et al (1992) 74 Moe et al ( 2008) 48 Cao et al (2019) 128 Mojiminiyi et al ( 2008) 49 Celikbilek et al (2014) 75 Pezzini et al (2002) 52 Cingozbay et al (2002) 76 Rahman et al (2013) 54 Coull et al (1990) 77 Tantirittisak et al (2007) 55 El Kossi and Zakhary (2000) 78 Vayá et al (2011) 57 Fatima et al (2012) 79 Yang et al (2004)…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Hiperhomosisteinemia diketahui berkaitan dengan meningkatnya risiko kardiovaskular 6 dan serebrovaskular. 7 Sebuah meta-analisis studi observasional menyimpulkan bahwa setiap peningkatan 2,5 µmol/L total plasma homosistein meningkatkan risiko infark miokard 10% dan meningkatkan risiko stroke 20%. 8 Asam folat berperan dalam metabolisme ANALISIS homosistein melalui siklus remetilasi.…”
Section: Pendahuluanunclassified
“…The studies show that hyperhomocysteinemia increases the chances of having a thromboembolic condition but it is still not clear which subtype of stroke is associated with hyperhomocysteinaemia [8]. In one of the studies, 75% of the ischemic stroke patients were found to have elevated fasting homocysteine levels [9] while in another study, 76.66% cases of ischemic stroke were revealed to have high fasting homocysteine levels as compared to normal people [10].…”
Section: Introductionmentioning
confidence: 99%